(untitled) (Al-Mansour Journal, 2022)
Abstract: Medically, heart rate is the number of Heart Pulses per minute. Blood pressure level detection is a technique developed here to detect the level of blood pressure every second (Normal, High or Low).The Heartbeat causes two invisible effects on human being. First, tiny motions in the human head (movement). Second, the blood that flow into skin cause a slight change in skin color (brightness). In this paper, an algorithm was proposed to detect the heartbeat from video depending on these effects (non-contact based system). Then the detected heart beat is used to measure the heart rate in per second (not in per minute) for unlimited time (video in any length) with Heart Wave drawing and detecting the level of blood pressure. The results show that this algorithm able to measure the heart rate and detect blood pressure level from Colored or Black and White Videos.